2005
DOI: 10.1002/art.21193
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of experimental spondylarthropathy

Abstract: PGIS, a murine model of autoimmune spondylitis, shows similarities to ankylosing spondylitis. Segregation of susceptibility to PG-induced arthritis (PGIA) from that to PGIS in different genetic crosses suggests that PGIA and PGIS are separate diseases. Therefore, this model allows for the elucidation of genetic components involved in the etiology of SpA, independent of those controlling the susceptibility to PGIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…Earlier we demonstrated that spondylitis susceptibility of mice of different parental strains and genetic crosses was associated with certain H-2-permissive haplotypes, which indicates the leading role of the MHC in murine arthritis and spondylitis (19). The major goal of this study was finding non-MHC genes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Earlier we demonstrated that spondylitis susceptibility of mice of different parental strains and genetic crosses was associated with certain H-2-permissive haplotypes, which indicates the leading role of the MHC in murine arthritis and spondylitis (19). The major goal of this study was finding non-MHC genes.…”
Section: Discussionmentioning
confidence: 92%
“…Clinical symptoms, histopathological and x-ray abnormalities, and the progression of the disease in PG-immunized mice, are very similar to those in human AS. As in human patients, inflammation in mice occurs first in sacroiliac joints occupied with enthesitis, and then expands upwards involving multiple IVDs (15,19).…”
Section: Hronic Inflammation Of the Axial Skeleton And Sacroiliac Jmentioning
confidence: 90%
“…Injection of PG in dimethyldioctadecylammonium bromide (DDA), a bipolar amphiphilic micelle-forming adjuvant, accelerated the onset of PG aggrecan-induced inflammation of the spine (PGIS) to 3 to 4 weeks after the third PG-DDA injection. Susceptible animals did not need additional PG injections, but the spondylitis still developed several weeks later than the peripheral arthritis [45].…”
Section: Pg Aggrecan-induced Inflammation Of the Spine And The Jointsmentioning
confidence: 99%
“…However, this tight correlation between PGIS and PGIA can be separated when different genetic backgrounds are combined (Table 2) [45]. For instance, F1 hybrids of the BALB/c x DBA/2 intercross were fully resistant to PGIA; however, more than 30% of these (BALB/c x DBA/2)F1 mice then developed PGIS.…”
Section: Pg Aggrecan-induced Inflammation Of the Spine And The Jointsmentioning
confidence: 99%
“…The genetic factors, excluding MHC-related genes, controlling axial disease were studied by crossing arthritis-susceptible BALB/c with MHC-matched arthritis-resistant DBA/2 mice [186]. Although spondylitis correlated with onset and severity of peripheral arthritis in BALB/c mice, axial disease became independent of peripheral arthritis after the F2 generation.…”
Section: -55 Il-23 Il-17 or Il-22 Overexpressionmentioning
confidence: 99%